-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathIFOL.agda
189 lines (152 loc) · 7.71 KB
/
IFOL.agda
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
{-# OPTIONS --prop --rewriting #-}
open import PropUtil
module IFOL (Term : Set) (R : Nat → Set) where
open import ListUtil
data Args : Nat → Set where
zero : Args 0
next : {n : Nat} → Args n → Term → Args (succ n)
data Form : Set where
Rel : {n : Nat} → R n → (Args n) → Form
_⇒_ : Form → Form → Form
_∧∧_ : Form → Form → Form
∀∀ : (Term → Form) → Form
⊤⊤ : Form
infixr 10 _∧∧_
infixr 8 _⇒_
Con = List Form
-- Proofs
private
variable
A B : Form
Γ Γ' Γ'' Δ : Con
n : Nat
r : R n
ts : Args n
data _⊢_ : Con → Form → Prop where
zero : A ∈ Γ → Γ ⊢ A
lam : (A ∷ Γ) ⊢ B → Γ ⊢ (A ⇒ B)
app : Γ ⊢ (A ⇒ B) → Γ ⊢ A → Γ ⊢ B
andi : Γ ⊢ A → Γ ⊢ B → Γ ⊢ (A ∧∧ B)
ande₁ : Γ ⊢ (A ∧∧ B) → Γ ⊢ A
ande₂ : Γ ⊢ (A ∧∧ B) → Γ ⊢ B
true : Γ ⊢ ⊤⊤
∀i : {F : Term → Form} → ({t : Term} → Γ ⊢ F t) → Γ ⊢ (∀∀ F)
∀e : {F : Term → Form} → Γ ⊢ (∀∀ F) → ( {t : Term} → Γ ⊢ (F t) )
-- We can add hypotheses to a proof
addhyp⊢ : Γ ∈* Γ' → Γ ⊢ A → Γ' ⊢ A
addhyp⊢ s (zero x) = zero (mon∈∈* x s)
addhyp⊢ s (lam h) = lam (addhyp⊢ (both∈* s) h)
addhyp⊢ s (app h h₁) = app (addhyp⊢ s h) (addhyp⊢ s h₁)
addhyp⊢ s (andi h₁ h₂) = andi (addhyp⊢ s h₁) (addhyp⊢ s h₂)
addhyp⊢ s (ande₁ h) = ande₁ (addhyp⊢ s h)
addhyp⊢ s (ande₂ h) = ande₂ (addhyp⊢ s h)
addhyp⊢ s (true) = true
addhyp⊢ s (∀i h) = ∀i (addhyp⊢ s h)
addhyp⊢ s (∀e h) = ∀e (addhyp⊢ s h)
-- Extension of ⊢ to contexts
_⊢⁺_ : Con → Con → Prop
Γ ⊢⁺ [] = ⊤
Γ ⊢⁺ (F ∷ Γ') = (Γ ⊢ F) ∧ (Γ ⊢⁺ Γ')
infix 5 _⊢⁺_
-- We show that the relation respects ∈*
mon∈*⊢⁺ : Γ' ∈* Γ → Γ ⊢⁺ Γ'
mon∈*⊢⁺ zero∈* = tt
mon∈*⊢⁺ (next∈* x h) = ⟨ (zero x) , (mon∈*⊢⁺ h) ⟩
-- The relation respects ⊆
mon⊆⊢⁺ : Γ' ⊆ Γ → Γ ⊢⁺ Γ'
mon⊆⊢⁺ h = mon∈*⊢⁺ (⊆→∈* h)
-- The relation is reflexive
refl⊢⁺ : Γ ⊢⁺ Γ
refl⊢⁺ {[]} = tt
refl⊢⁺ {x ∷ Γ} = ⟨ zero zero∈ , mon⊆⊢⁺ (next⊆ zero⊆) ⟩
-- We can add hypotheses to to a proof
addhyp⊢⁺ : Γ ∈* Γ' → Γ ⊢⁺ Γ'' → Γ' ⊢⁺ Γ''
addhyp⊢⁺ {Γ'' = []} s h = tt
addhyp⊢⁺ {Γ'' = x ∷ Γ''} s ⟨ Γx , ΓΓ'' ⟩ = ⟨ addhyp⊢ s Γx , addhyp⊢⁺ s ΓΓ'' ⟩
-- The relation respects ⊢
halftran⊢⁺ : {Γ Γ' : Con} → {F : Form} → Γ ⊢⁺ Γ' → Γ' ⊢ F → Γ ⊢ F
halftran⊢⁺ {Γ' = F ∷ Γ'} h⁺ (zero zero∈) = proj₁ h⁺
halftran⊢⁺ {Γ' = F ∷ Γ'} h⁺ (zero (next∈ x)) = halftran⊢⁺ (proj₂ h⁺) (zero x)
halftran⊢⁺ h⁺ (lam h) = lam (halftran⊢⁺ ⟨ (zero zero∈) , (addhyp⊢⁺ (right∈* refl∈*) h⁺) ⟩ h)
halftran⊢⁺ h⁺ (app h h₁) = app (halftran⊢⁺ h⁺ h) (halftran⊢⁺ h⁺ h₁)
halftran⊢⁺ h⁺ (andi hf hg) = andi (halftran⊢⁺ h⁺ hf) (halftran⊢⁺ h⁺ hg)
halftran⊢⁺ h⁺ (ande₁ hfg) = ande₁ (halftran⊢⁺ h⁺ hfg)
halftran⊢⁺ h⁺ (ande₂ hfg) = ande₂ (halftran⊢⁺ h⁺ hfg)
halftran⊢⁺ h⁺ (true) = true
halftran⊢⁺ h⁺ (∀i h) = ∀i (halftran⊢⁺ h⁺ h)
halftran⊢⁺ h⁺ (∀e h {t}) = ∀e (halftran⊢⁺ h⁺ h)
-- The relation is transitive
tran⊢⁺ : {Γ Γ' Γ'' : Con} → Γ ⊢⁺ Γ' → Γ' ⊢⁺ Γ'' → Γ ⊢⁺ Γ''
tran⊢⁺ {Γ'' = []} h h' = tt
tran⊢⁺ {Γ'' = x ∷ Γ*} h h' = ⟨ halftran⊢⁺ h (proj₁ h') , tran⊢⁺ h (proj₂ h') ⟩
{--- DEFINITIONS OF ⊢⁰ and ⊢* ---}
-- ⊢⁰ are neutral forms
-- ⊢* are normal forms
data _⊢⁰_ : Con → Form → Prop
data _⊢*_ : Con → Form → Prop
data _⊢⁰_ where
zero : A ∈ Γ → Γ ⊢⁰ A
app : Γ ⊢⁰ (A ⇒ B) → Γ ⊢* A → Γ ⊢⁰ B
ande₁ : Γ ⊢⁰ A ∧∧ B → Γ ⊢⁰ A
ande₂ : Γ ⊢⁰ A ∧∧ B → Γ ⊢⁰ B
∀e : {F : Term → Form} → Γ ⊢⁰ (∀∀ F) → ( {t : Term} → Γ ⊢⁰ (F t) )
data _⊢*_ where
neu⁰ : Γ ⊢⁰ Rel r ts → Γ ⊢* Rel r ts
lam : (A ∷ Γ) ⊢* B → Γ ⊢* (A ⇒ B)
andi : Γ ⊢* A → Γ ⊢* B → Γ ⊢* (A ∧∧ B)
∀i : {F : Term → Form} → ({t : Term} → Γ ⊢* F t) → Γ ⊢* ∀∀ F
true : Γ ⊢* ⊤⊤
infix 5 _⊢⁰_
infix 5 _⊢*_
-- We can add hypotheses to a proof
addhyp⊢⁰ : Γ ∈* Γ' → Γ ⊢⁰ A → Γ' ⊢⁰ A
addhyp⊢* : Γ ∈* Γ' → Γ ⊢* A → Γ' ⊢* A
addhyp⊢⁰ s (zero x) = zero (mon∈∈* x s)
addhyp⊢⁰ s (app h h₁) = app (addhyp⊢⁰ s h) (addhyp⊢* s h₁)
addhyp⊢⁰ s (ande₁ h) = ande₁ (addhyp⊢⁰ s h)
addhyp⊢⁰ s (ande₂ h) = ande₂ (addhyp⊢⁰ s h)
addhyp⊢⁰ s (∀e h {t}) = ∀e (addhyp⊢⁰ s h) {t}
addhyp⊢* s (neu⁰ x) = neu⁰ (addhyp⊢⁰ s x)
addhyp⊢* s (lam h) = lam (addhyp⊢* (both∈* s) h)
addhyp⊢* s (andi h₁ h₂) = andi (addhyp⊢* s h₁) (addhyp⊢* s h₂)
addhyp⊢* s true = true
addhyp⊢* s (∀i h) = ∀i (addhyp⊢* s h)
-- Extension of ⊢⁰ to contexts
-- i.e. there is a neutral proof for any element
_⊢⁰⁺_ : Con → Con → Prop
Γ ⊢⁰⁺ [] = ⊤
Γ ⊢⁰⁺ (F ∷ Γ') = (Γ ⊢⁰ F) ∧ (Γ ⊢⁰⁺ Γ')
infix 5 _⊢⁰⁺_
-- The relation respects ∈*
mon∈*⊢⁰⁺ : Γ' ∈* Γ → Γ ⊢⁰⁺ Γ'
mon∈*⊢⁰⁺ zero∈* = tt
mon∈*⊢⁰⁺ (next∈* x h) = ⟨ (zero x) , (mon∈*⊢⁰⁺ h) ⟩
-- The relation respects ⊆
mon⊆⊢⁰⁺ : Γ' ⊆ Γ → Γ ⊢⁰⁺ Γ'
mon⊆⊢⁰⁺ h = mon∈*⊢⁰⁺ (⊆→∈* h)
-- This relation is reflexive
refl⊢⁰⁺ : Γ ⊢⁰⁺ Γ
refl⊢⁰⁺ {[]} = tt
refl⊢⁰⁺ {x ∷ Γ} = ⟨ zero zero∈ , mon⊆⊢⁰⁺ (next⊆ zero⊆) ⟩
-- A useful lemma, that we can add hypotheses
addhyp⊢⁰⁺ : Γ ∈* Γ' → Γ ⊢⁰⁺ Γ'' → Γ' ⊢⁰⁺ Γ''
addhyp⊢⁰⁺ {Γ'' = []} s h = tt
addhyp⊢⁰⁺ {Γ'' = A ∷ Γ'} s ⟨ Γx , ΓΓ'' ⟩ = ⟨ addhyp⊢⁰ s Γx , addhyp⊢⁰⁺ s ΓΓ'' ⟩
-- The relation preserves ⊢⁰ and ⊢*
halftran⊢⁰⁺* : {Γ Γ' : Con} → {F : Form} → Γ ⊢⁰⁺ Γ' → Γ' ⊢* F → Γ ⊢* F
halftran⊢⁰⁺⁰ : {Γ Γ' : Con} → {F : Form} → Γ ⊢⁰⁺ Γ' → Γ' ⊢⁰ F → Γ ⊢⁰ F
halftran⊢⁰⁺* h⁺ (neu⁰ x) = neu⁰ (halftran⊢⁰⁺⁰ h⁺ x)
halftran⊢⁰⁺* h⁺ (lam h) = lam (halftran⊢⁰⁺* ⟨ zero zero∈ , addhyp⊢⁰⁺ (right∈* refl∈*) h⁺ ⟩ h)
halftran⊢⁰⁺* h⁺ (andi h₁ h₂) = andi (halftran⊢⁰⁺* h⁺ h₁) (halftran⊢⁰⁺* h⁺ h₂)
halftran⊢⁰⁺* h⁺ true = true
halftran⊢⁰⁺* h⁺ (∀i h) = ∀i (halftran⊢⁰⁺* h⁺ h)
halftran⊢⁰⁺⁰ {Γ' = x ∷ Γ'} h⁺ (zero zero∈) = proj₁ h⁺
halftran⊢⁰⁺⁰ {Γ' = x ∷ Γ'} h⁺ (zero (next∈ h)) = halftran⊢⁰⁺⁰ (proj₂ h⁺) (zero h)
halftran⊢⁰⁺⁰ h⁺ (app h h') = app (halftran⊢⁰⁺⁰ h⁺ h) (halftran⊢⁰⁺* h⁺ h')
halftran⊢⁰⁺⁰ h⁺ (ande₁ h) = ande₁ (halftran⊢⁰⁺⁰ h⁺ h)
halftran⊢⁰⁺⁰ h⁺ (ande₂ h) = ande₂ (halftran⊢⁰⁺⁰ h⁺ h)
halftran⊢⁰⁺⁰ h⁺ (∀e h {t}) = ∀e (halftran⊢⁰⁺⁰ h⁺ h)
-- The relation is transitive
tran⊢⁰⁺ : {Γ Γ' Γ'' : Con} → Γ ⊢⁰⁺ Γ' → Γ' ⊢⁰⁺ Γ'' → Γ ⊢⁰⁺ Γ''
tran⊢⁰⁺ {Γ'' = []} h h' = tt
tran⊢⁰⁺ {Γ'' = x ∷ Γ} h h' = ⟨ halftran⊢⁰⁺⁰ h (proj₁ h') , tran⊢⁰⁺ h (proj₂ h') ⟩